Sustainable indicator for feature attributes assessment of urban green space / Rabi'ah Ahmad and Abdul Nassir Matori - Rabi'ah, Ahmad; Abdul Nassir, Matori (2015)
Urban green space features are natural or human-made facilities commonly found in community or recreational parks.Green features attributes such as size, design, usage, location and facilities are very influential in determining the satisfaction level of park users or visitors. There is a need to study the physical environment of green space that can be associated with the aspirations and demands of park users. For that reason, this research performed a study to design and develop a model for urban green space feature attributes. Two prominent recreational parks in Ipoh city have been chosen as a case study and the research investigates the influence of attributes features towards the needs of urban green space. The influence and effectiveness are measured using an integrated GIS mapping approach with qualitative assessments on satisfactory level of park visitors with the feature attributes available in both parks. A geo-referenced classified map of feature attributes of the recreational parks under study is initially prepared. Subsequentlyin the qualitative assessment, the variables measured on the physical and natural characters of the parks suggested that diversity of feature attributes for urban green space supports the social interaction for all age group. A sustainable indicator that defines the importance of urban green space feature components is proposed in defining the future Malaysian National Urbanisation Policy.